2017
DOI: 10.4239/wjd.v8.i6.297
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for low high-density lipoprotein among Asian Indians in the United States

Abstract: AIMTo examine the differences in metabolic risk factors (RFs) by gender in the Asian Indian (AI) population in the United States.METHODSUsing cross-sectional data from 1038 randomly selected Asian Indians, we investigated the relationship between metabolic syndrome (MetS) RFs, cardiovascular disease, and diabetes.RESULTSA greater percent of women in this group had increased waist circumference and low high density lipoprotein (HDL) levels than men, but AI males had increased blood glucose, increased blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The mean fluorescence intensity (MFI) of TCRβ on CD8 SP T-cells was reduced in infected thymi, consistent with activation-induced TCR downregulation (Fig. 5D) (26). We further found that these cells were positive for KLRG1, CD69, and CD44 while having decreased expression of CD62L, as compared to CD8 SP thymocytes from uninfected mice, consistent with effector T cells (Fig.…”
Section: Resultssupporting
confidence: 72%
“…The mean fluorescence intensity (MFI) of TCRβ on CD8 SP T-cells was reduced in infected thymi, consistent with activation-induced TCR downregulation (Fig. 5D) (26). We further found that these cells were positive for KLRG1, CD69, and CD44 while having decreased expression of CD62L, as compared to CD8 SP thymocytes from uninfected mice, consistent with effector T cells (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Survey data were collected via telephone interviews by trained, multilingual AI staff; the response rate was 37%. Although the response rate of 37% is relatively low for an epidemiologic study, it is similar to or higher than the response rate in published health surveys of Asians, Asian Indians, or immigrant ethnic groups [ 12 , 31 ]. The possible reasons for a 37% response rate might be (a) voluntary participation; (b) reluctance to divulge personal information and provide fasting serum blood; (c) not attributing any value to research studies that require time to complete surveys and fasting blood work; (d) ability to understand the purpose and benefits of the study; and (d) barriers associated with confidentiality, trust, and safety.…”
Section: Methodsmentioning
confidence: 65%
“…The sample consisted of 1038 randomly selected Asian Indians, aged 18 years and older, from seven US cities—Houston, TX; Phoenix, AZ; Washington, DC; Boston, MA; San Diego, CA; Edison, NJ; and Parsippany, NJ. The sampling procedure and data collection methodology were reported in prior publications [ 12 , 31 ]. Participation was voluntary.…”
Section: Methodsmentioning
confidence: 99%
“…Low HDL (99.9%) was a common abnormality amongst women and the least common abnormality amongst males (10%). The prevalence of low HDL amongst Asian Indians has been validated by various studies (17) (18). Low HDL is a strong predictor of MI and stroke and is strongly associated with wish CAD.…”
Section: Discussionmentioning
confidence: 98%